2016
DOI: 10.1097/grf.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Length Screening in Asymptomatic Women at High Risk and Low Risk for Spontaneous Preterm Birth

Abstract: Cervical length (CL) screening should be offered to singletons because there are interventions for those with a short CL. A transvaginal ultrasound (TVU) is the ''gold standard'' for CL. In singletons with prior spontaneous preterm birth, serial TVU CL screening isrecommended between16and236/7weeks. Universal TVU CL screening between 18 and 24 weeks may be considered for low-risk singletons with the administration of vaginal progesterone for TVU CLr20 mm; alternatively, transabdominal ultrasound CL screening m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
2
4
0
1
Order By: Relevance
“…The lower proportion of women with short secondtrimester CL in this study is, however, in accordance with recent large studies on screening programs at 18-23 weeks [26][27][28] . In a low-risk population of 1569 women, 1.1% had CL < 20 mm and there was no difference in risk of spontaneous PTD between women undergoing and not undergoing screening 28 . Likewise, Miller et al 27 reported a 0.9% incidence of CL ≤ 25 mm among 18 250 women at 20 weeks.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The lower proportion of women with short secondtrimester CL in this study is, however, in accordance with recent large studies on screening programs at 18-23 weeks [26][27][28] . In a low-risk population of 1569 women, 1.1% had CL < 20 mm and there was no difference in risk of spontaneous PTD between women undergoing and not undergoing screening 28 . Likewise, Miller et al 27 reported a 0.9% incidence of CL ≤ 25 mm among 18 250 women at 20 weeks.…”
Section: Discussionsupporting
confidence: 93%
“…Our data support the literature suggesting that universal CL screening in the second trimester may not be as cost-effective as believed previously, as it is highly dependent on the proportion of short CL and the rate of spontaneous PTD [26][27][28]32 . In our population, if CL screening was implemented at the 19-21-week anomaly scan, the NNS to prevent one spontaneous PTD < 34 weeks was more than 1500 women.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In low-risk pregnant women, mean CL at 14-30 weeks of gestation varies from 35 to 4mm, with the 10th percentile being 25mm and 90th percentile being 50mm [8]. In asymptomatic women after 30 gestational weeks, the cervix physiologically shortens and CL less than 25mm does not indicate preterm labor [9]. It seems that initial screening for preterm delivery should start between 18 and 22 weeks of gestation, because in most women who deliver before 37 weeks a short cervix is detected at that time [8].…”
Section: Kmentioning
confidence: 99%
“…Por tanto, surge la imperiosa necesidad de desarrollar estrategias efectivas para tamizaje y prevención de parto pretérmino en la población de mujeres embarazadas, con o sin factores de riesgo (1, 2). En la actualidad se considera que un cuello uterino corto en el segundo trimestre es nuestro mejor predictor de síndrome de parto pretérmino (10,11). Aunque el tratamiento de cérvix corto sigue siendo controvertido a pesar de más de 600 publicaciones en las últimas 2 décadas sobre la relación entre síndrome de parto pretérmino, cuello uterino corto y las intervenciones propuestas (5).…”
Section: Métodos Diagnósticosunclassified